Alexandre Lamfalussy and the origins of instability in capitalist economies - Ivo Maes (National Bank of Belgium, 2023)
In this paper the vision of the "Young" and "Elder" Lamfalussy on the origins of instability in capitalist economies will be contrasted. The young Lamfalussy found the origins of instability in medium-term cumulative processes in the real sector of the economy, very much inspired by the vicious circles in the British and Belgian economies in the postwar period, in contrast to the virtuous growth processes of the German and Italian economies. The Elder Lamfalussy focused on financial innovations and the short-term myopic behavior of financial markets, very much inspired by his experience of the Latin American debt build-up and ensuing crisis in the early 1980s. The Euro area crisis showed the importance of both processes, as it was the consequence of both short-term myopic behavior in financial markets and medium-term cumulative processes in the real sector.
Keywords: A11; B22; B32; E3; E 60; F02; G10; N10; 330; Lamfalussy; economic instability; economic cycles; financial innovations; Latin American debt crisis; Euro area crisis